Mobile Web and Intelligent Information Systems : 12th International Conference, MobiWis 2015, Rome, Italy, August 24-26, 2015, Proceedings - Younas, Muhammad; Awan, Irfan; Mecella, Massimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 12th International Conference on Mobile Web and Intelligent Information Systems, MobiWIS 2015, held in Rome, Italy, in August 2015. The 17 full papers and 3 short papers presented were carefully reviewed and selected from 55 submissions. The papers are organized in topical sections such as mobile services and applications; usability and visualization; mobile networks and applications; mobile data services; smart phones and mobile commerce applications.
Mobile services and applications -- Usability and visualization -- Mobile networks and applications -- Mobile data services -- Smart phones and mobile commerce applications.
Keywords: Computer Communication Networks; Software engineering; Computer science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Software Engineering; e-Commerce/e-business.; Computers and Society